Comprehensive Approach to the Management of Patients with Recurrent Corneal Erosions - A. V. Doga; N. V. Maychuk; I. A. Mushkova; I. A. Babitskaya (Oftalʹmologiâ)
In the Russian literature, there are only a few works that summarize their own experience in the treatment of recurrent corneal erosion (RCE) in a limited group of patients, which actualizes further research in this direction.Objective: to develop and evaluate the clinical effectiveness of an integrated approach to the management of patients with RCE.Patients and methods. 69 patients (69 eyes) with RCE and a disease duration of at least two years, who were divided into 3 groups according to the frequency of relapses: group 1 (12 people) — episodes of RCE no more than 2–4 times a year; Group 2 (19 people) — RCE episodes no more than once a month; Group 3 (38 people) — RCE episodes more than 2 times a month. All patients were cured by pharmacological support, if conservative therapy was ineffective (1 relapse during treatment within 1 month), phototherapeutic keratectomy (PTK) was performed with the application of a bandage contact lens and the appointment of pathogenetically-oriented treatment for up to 1 year. The average follow-up period was 28.6 ± 6.1 months.Results and discussion. In group 1, during the entire period of observation, RCE was compensated by the therapy, in the other groups, the effectiveness was lower, which in 41 (59.4 %) cases required the implementation of PTK. There were no relapses of corneal erosion after PTK with subsequent pathogenetically-oriented therapy, including heparin-containing medications in instillation (CHYLOPARIN-KOMOD®) and ointment forms (PARIN-POS®) for 1 year.Conclusion. The high effectiveness of PTK with subsequent pathogenetically-oriented pharmacological support may be the basis for a broader recommendation of this method in patients with RCE and a relapse rate of more than 1 time a month.